Interplay Between Iron Overload and Osteoarthritis: Clinical Significance and Cellular Mechanisms - Cai, Chenhui; Hu, Wenhui; Chu, Tongwei (Frontiers in Cell and Developmental Biology, 2022)
There are multiple diseases or conditions such as hereditary hemochromatosis, hemophilia, thalassemia, sickle cell disease, aging, and estrogen deficiency that can cause iron overload in the human body. These diseases or conditions are frequently associated with osteoarthritic phenotypes, such as progressive cartilage degradation, alterations in the microarchitecture and biomechanics of the subchondral bone, persistent joint inflammation, proliferative synovitis, and synovial pannus. Growing evidences suggest that the conditions of pathological iron overload are associated with these osteoarthritic phenotypes. Osteoarthritis (OA) is an important complication in patients suffering from iron overload-related diseases and conditions. This review aims to summarize the findings and observations made in the field of iron overload-related OA while conducting clinical and basic research works. OA is a whole-joint disease that affects the articular cartilage lining surfaces of bones, subchondral bones, and synovial tissues in the joint cavity. Chondrocytes, osteoclasts, osteoblasts, and synovial-derived cells are involved in the disease. In this review, we will elucidate the cellular and molecular mechanisms associated with iron overload and the negative influence that iron overload has on joint homeostasis. The promising value of interrupting the pathologic effects of iron overload is also well discussed for the development of improved therapeutics that can be used in the field of OA.